Catalyst Ni0. 7Zn0. 3O / C-x for producing hydrogen peroxide through two-electron oxygen reduction and preparation method thereof

Through the preparation of the new NiZn-MOF catalyst material, the problems of low performance and high cost of alkali cathode oxygen reduction reaction catalysts in the prior art are solved, and efficient and low-cost preparation of hydrogen peroxide is achieved, and the catalyst stability is improved.

CN119710810APending Publication Date: 2025-03-28HEILONGJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510091781.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, the electrocatalytic performance of alkali cathodic oxygen reduction reaction catalysts is low, the precious metal catalysts are costly and have insufficient stability.

Method used

A new NiZn-MOF catalyst material is prepared by a one-step wet method, and the Ni0.7Zn0.3O/C-450 catalyst is prepared by a one-step wet method. The unique atomic arrangement method of NiZn-MOF and the combination of carbon groups are used to improve the active site and conductivity of the catalyst.

Benefits of technology

It has achieved efficient preparation of hydrogen peroxide, with H2O2 selectivity reaching 99%, electron transfer number close to 2, and Faraday efficiency reaching 90%, extending the service life of the catalyst and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for using Ni0. 7Zn0. 3O / C as a two-electron oxygen reduction reaction (2e-ORR) catalytic material. The material is synthesized through a specific preparation process, and has unique crystal structure and electronic characteristics. In the ORR process, Ni0. 7Zn0. 3O / C shows excellent two-electron catalytic activity, and can efficiently catalyze and reduce oxygen into hydrogen peroxide (H2O2). The catalytic material has good stability and selectivity, a novel, efficient and potential catalytic material selection is provided for development of related electrochemical technologies, and further innovation and breakthrough of the electrochemical field in the aspects of energy conversion and substance synthesis are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an alkaline cathode oxygen reduction reaction catalyst material. Technical Background

[0002] Hydrogen peroxide (H2O2) is widely used in the electronics industry, textile and paper bleaching, household and medical disinfection, and wastewater treatment, and has important application value. However, traditional H2O2 industrial production methods, such as the anthraquinone method, have many problems such as high energy consumption, cumbersome steps, the need for precious metal catalysts, and the production of toxic byproducts. In addition, large-scale production equipment makes it difficult to achieve decentralized production, and there are storage and transportation safety risks. As the world's attention to environmental pollution continues to increase, it is crucial to develop efficient and green chemical processes. 2e - The ORR process for producing H2O2 is a green and efficient alternative strategy with the advantages of high safety, environmental friendliness, and decentralized production. It has attracted widespread attention, and the preparation of cathode catalysts during the reaction is one of the key factors in the process.

[0003] Metal-organic framework (MOF)-derived catalysts have high specific surface area, tunable pore structure and abundant metal active sites. Catalysts prepared with MOF as precursor or template have a high specific surface area, tunable pore structure and abundant metal active sites. - MOF-derived catalysts can effectively inherit the structural characteristics and active sites of MOF, providing a favorable environment for the adsorption and reduction of oxygen. However, there are still problems such as poor conductivity, low catalytic efficiency, and insufficient stability. Therefore, it is crucial to design and study new MOF catalysts and develop better synthesis methods to further improve their catalytic activity and selectivity for the application of electrocatalytic synthesis of H2O2.

[0004] This invention innovatively proposes a new NiZn-MOF preparation strategy. This method not only provides a new method for the decomposition of 2e - The many difficulties faced in the ORR process have opened up a new path of thinking, and the efficient preparation of H2O2 has been achieved under green, environmentally friendly, safe and reliable conditions, which has strongly promoted the 2e - Further development and application expansion of ORR technology. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of low electrocatalytic performance and high cost of precious metal catalysts in the preparation of hydrogen peroxide by alkaline cathode oxygen reduction reaction in the prior art, and to provide a catalyst Ni suitable for cathode oxygen reduction reaction. 0.7 Zn 0.3 Preparation method of O-450.

[0006] A Ni 0.7 Zn0.3 Ox2e - The ORR catalyst material is a composite material prepared from a zinc source and a nickel source, and the calcination temperature is 350°C, 450°C, or 550°C.

[0007] A Ni 0.7 Zn 0.3 The preparation method of O / Cx catalyst material is specifically carried out according to the following steps: 1) Preparation of NiZn-MOF: 35 mg zinc nitrate, 52 mg nickel acetate, and 16.8 mg terephthalic acid are dispersed in 25.6 ml of a solution containing DMAC and anhydrous ethanol, and stirred at room temperature for 10 min. The solution is transferred to a 100 ml polytetrafluoroethylene stainless steel autoclave and maintained in a hydrothermal oven at a reaction temperature of 120 ° C for 3 h. After cooling to room temperature, it is washed with DMAC and anhydrous ethanol. The collected samples are dried in an oven at 60 ° C for 12 h to obtain a green powder solid sample, that is, NiZn-MOF is obtained; 2) NiZn-MOF carbonization treatment: The NiZn-MOF obtained in step 1) is evenly spread in a covered corundum porcelain boat, placed in a tubular furnace, heated to 450 ° C at a heating rate of 5 ° C / min and kept warm for 1 h. After heating, it is cooled to room temperature, and the carbonized sample is taken out to obtain NiZn-MOF-derived carbon, called Ni 0.7 Zn 0.3 O / C-450; 3) using a standard three-electrode system in an H-type reactor with a proton exchange membrane as a diaphragm, the catalyst obtained in step 2) is used as the working electrode, SCE is used as the reference electrode, the Pt sheet is used as the counter electrode, the electrolytic cell solution is 120 mL of 0.1 M O2-saturated KOH solution, and O2 is continuously introduced during the reaction process. H2O2 is synthesized by electrocatalytic reaction at a voltage of 0.5 V (vs. RHE) for 1 h.

[0008] In the above step 1), the ratio of ethanol to deionized water in the 25.6 mL mixed solution of DMAC and anhydrous ethanol is 2:1. The present invention has the following beneficial effects:

[0009] The Ni prepared by the present invention 0.7 Zn 0.3 O / C-450 2e - The ORR catalyst is prepared by a simple one-pot wet method. Its unique atomic arrangement makes it possible to expose more atoms with specific coordination environments on the crystal surface, providing abundant and unique active sites for the ORR reaction, which is beneficial to the adsorption and activation of oxygen molecules and promotes the 2e - ORR process.

[0010] The Ni prepared by the present invention 0.7 Zn 0.3 O / C-450 2e- A series of performance tests of the ORR catalyst material showed that the H2O2 selectivity can reach 99% and the electron transfer number is close to 2. In the H-type electrolytic cell test, the Faraday efficiency is 90% and the H2O2 yield is 4.5 mol, which has excellent ORR activity.

[0011] The Ni prepared by the present invention 0.7 Zn 0.3 O / C-450 2e - ORR catalyst materials can better maintain their structural integrity during long-term electrochemical processes, resist electrolyte erosion and reconstruction of the electrode surface, enable the catalyst to maintain good catalytic performance during long-term reaction processes, extend the service life of the catalyst and reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The carbonized ZnO / C 2e prepared in Example 1 - ORR catalyst materials (a) and Ni 0.7 Zn 0.3 O / C 2e - SEM image of ORR catalyst material (b);

[0013] Figure 2 Ni prepared in Example 1 0.7 Zn 0.3 O / C 2e - TEM image of ORR catalyst material;

[0014] Figure 3 Ni prepared in Example 1 0.7 Zn 0.3 O / C 2e - XRD patterns of ORR catalyst materials;

[0015] Figure 4 Ni prepared in Example 1 0.7 Zn 0.3 O / C 2e - XPS spectrum of ORR catalyst material;

[0016] Figure 5 2e prepared in Example 1 and Comparative Examples 1, 2, 3, and 4 - CV graph of ORR catalyst material;

[0017] Figure 6 2e prepared in Example 1 and Comparative Examples 1, 2, 3, and 4 - Transfer electron number and H2O2 selectivity diagram of ORR catalyst materials;

[0018] Figure 7Ni prepared in Example 1 0.7 Zn 0.3 O / C 2e - Faradaic efficiency and H2O2 yield of ORR catalyst materials at different potentials; DETAILED DESCRIPTION

[0020] Example 1

[0021] Ni 0.7 Zn 0.3 The preparation method of O / C-450 oxygen reduction reaction catalyst material is specifically carried out according to the following steps: (1) Disperse 35 mg zinc nitrate, 52 mg nickel acetate, and 16.8 mg terephthalic acid in 25.6 ml of a solution containing DMAC and ethanol, and stir at room temperature for 10 minutes. Transfer the solution to a 100 ml polytetrafluoroethylene stainless steel autoclave and keep it in a hydrothermal oven at a reaction temperature of 120°C for 3 hours. After cooling to room temperature, wash it with DMAC and anhydrous ethanol. The collected sample is dried in an oven at 60°C for 12 hours to obtain a green powder solid sample, that is, NiZn-MOF. (2) Spread the NiZn-MOF obtained in the previous step evenly in a covered corundum porcelain boat, put it into a tubular furnace, heat it to 450°C at a heating rate of 5°C / min and keep it warm for 1 hour. After heating, cool it to room temperature, take out the carbonized sample, and obtain NiZn-MOF-derived carbon, called Ni 0.7 Zn 0.3 O / C-450.

[0022] Comparative Example 1

[0023] ZnO / C is specifically prepared according to the following steps: In step 1, only 97.19 mg zinc nitrate and 16.8 mg terephthalic acid are added to 25.6 ml of a solution containing DMAC and ethanol, and stirred at room temperature for 10 min. The solution is transferred to a 100 ml polytetrafluoroethylene stainless steel autoclave and kept in a hydrothermal oven at a reaction temperature of 120 ° C for 3 h. After cooling to room temperature, DMAC and anhydrous ethanol are used for washing. The collected samples are dried in an oven at 60 ° C for 12 h to obtain a green powdered solid sample, that is, NiZn-MOF is obtained. The remaining steps are the same as in Example 1.

[0024] Comparative Example 2

[0025] NiO / C-450 is specifically carried out according to the following steps: In step 1, only 81.30 mg of nickel acetate and 16.8 mg of terephthalic acid are added to 25.6 ml of a solution containing DMAC and ethanol, and stirred at room temperature for 10 min. The solution is transferred to a 100 ml polytetrafluoroethylene stainless steel autoclave and kept in a hydrothermal oven at a reaction temperature of 120 ° C for 3 h. After cooling to room temperature, it is washed with DMAC and anhydrous ethanol. The collected samples are dried in an oven at 60 ° C for 12 h to obtain a green powder solid sample, that is, NiZn-MOF is obtained. The remaining steps are the same as 1.

[0026] Comparative Example 3

[0027] Ni 0.7 Zn 0.3 O / C-350 is specifically carried out in the following steps: Step 1 is the same as Example 1, except that Step 2 is: the NiZn-MOF obtained in the previous step is evenly spread in a covered corundum porcelain boat, placed in a tube furnace, heated to 350°C at a heating rate of 5°C / min and kept warm for 1h, cooled to room temperature after the heating, and the carbonized sample is taken out to obtain NiZn-MOF derived carbon, called Ni 0.7 Zn 0.3 O / C-350.

[0028] Comparative example 4.

[0029] Ni 0.7 Zn 0.3 O / C-550 is specifically carried out in the following steps: Step 1 is the same as Example 1, except that Step 2 is: the NiZn-MOF obtained in the previous step is evenly spread in a covered corundum porcelain boat, placed in a tube furnace, heated to 550°C at a heating rate of 5°C / min and kept warm for 1h, cooled to room temperature after the heating, and the carbonized sample is taken out to obtain NiZn-MOF derived carbon, called Ni 0.7 Zn 0.3 O / C-550.

[0030] The catalyst obtained in the above manner was subjected to electrochemical testing to verify the catalyst performance, and 0.1 M KOH (alkaline) was used as the electrolyte solution in all tests.

[0031] Preparation of electrochemical working electrode: 5.0 mg of catalyst was weighed and mixed with 100 μL of ethanol and 50 μL of Nafion (5wt.%) and ultrasonicated for 0.5 h to prepare a uniform catalyst ink. 3 μL of the prepared catalyst ink was evenly coated on the glassy carbon electrode to obtain a loading mass of 0.1 mg. The glassy carbon area of ​​the rotating disk electrode and the rotating ring disk electrode was the same. The ORR performance of the catalyst was evaluated using an electrochemical workstation (CHI760E, Shanghai Chenhua Instrument Co., Ltd.) in an oxygen-saturated 0.1 M KOH solution using a rotating disk electrode.

[0032] Ni 0.7 Zn 0.3 Preparation of O / Cx cathode electrode: Weigh 10 mg of catalyst, 40 uL Nafion (5 wt.%), 120 uL isopropanol, and 40 microliters of DI, mix and ultrasonicate for 1 h to prepare a uniform catalyst ink. The prepared ink is evenly coated on the surface of carbon paper to make the loading amount 1 mg cm -1 .

[0033] Specific embodiments 1 to 6 of the catalytic materials and their corresponding characterization and performance analysis:

[0034] Figure 1 (a) The scanning electron microscope (SEM) image of ZnO / C shown shows specific morphological features. In this image, cubic structures with surface roughness can be clearly observed, with a size of approximately 20 nm. These cubic structures show a relatively regular geometric morphology, and the roughness of their surfaces suggests that they may have undergone a complex crystallization or growth process during their formation, resulting in surface unevenness at the microscopic level. When zinc nitrate and nickel acetate are added to the system at the same time, the resulting Ni 0.7 Zn 0.3 The morphology of O / C-450 has changed significantly, as shown in Figure 1 (b). The originally regular cubic structure has broken into smaller nanoparticles. This transformation from cubic to nanoparticles fully demonstrates that the introduction of nickel may have changed the crystal growth kinetics of the material, destroyed the stability of the original ZnO / C cubic structure, and caused it to recrystallize or reconstruct under new conditions, ultimately forming a nanoparticle morphology with a smaller size and possibly changed dispersibility.

[0035] Figure 2The XRD spectra of all samples clearly show the different products generated when different metal salts are added. In the system where only zinc nitrate is added, the corresponding XRD spectrum shows a diffraction peak pattern that is completely consistent with the characteristic peak of ZnO, which indicates that under this specific condition, the reaction product is ZnO. When only nickel nitrate is added to the system, the XRD spectrum only shows the diffraction peak characteristics unique to NiO. The position, intensity and peak shape of these diffraction peaks are consistent with the standard XRD spectrum characteristics of NiO, which means that under this experimental condition, the reaction generates NiO alone. In the system where zinc nitrate and nickel nitrate are added at the same time, the XRD spectrum shows a diffraction peak pattern that is consistent with Ni 0.7 Zn 0.3 Unique diffraction peak combination corresponding to O / C.

[0036] Figure 3 This is the XPS energy spectrum of Example 1, and the peaks of Ni, Zn, C, O, and N elements can be observed, which is consistent with the XRD test results.

[0037] Figure 4 The cyclic voltammetry (CV) curves of all samples are presented. A significant reduction peak can be clearly observed at a potential of 0.6 V. The appearance of the reduction peak at this specific potential confirms that the reaction process in the reaction system is an oxygen reduction reaction.

[0038] Figure 5 Figure 2 is the electron transfer number (n) and H2O2 selectivity of all samples. It can be clearly observed that Ni 0.7 Zn 0.3 The n of O / C is close to 2, and the H2O2 selectivity is 98.5%, which is significantly better than other samples, indicating that this sample has good 2e - ORR activity.

[0039] Figure 6 The variation trend of Faraday efficiency and H2O2 yield under different voltage conditions is shown in Figure 2. It can be found that when the voltage is 0.5V, the Faraday efficiency reaches 90%. At the same time, the yield of H2O2 under this voltage is 4.3mol, indicating that the catalyst has excellent catalytic performance with high selectivity and high activity for the synthesis reaction of H2O2 under the voltage condition of 0.5V.

[0040] Figure 7 Ni 0.7 Zn 0.3 On-site photo of O / C's H-type electrolytic cell.

Claims

1. A 2e - The preparation method of ORR catalyst is characterized in that 2e - The preparation of ORR catalyst is achieved by the following steps: (1) Disperse a certain amount of zinc nitrate, nickel acetate, and terephthalic acid into a solution containing DMAC and ethanol, and stir at room temperature for 10 minutes. (2) Transfer the solution to a 100 ml polytetrafluoroethylene stainless steel autoclave and keep it in a hydrothermal oven at a reaction temperature of 120°C for 3 hours. After cooling to room temperature, wash it with DMAC and anhydrous ethanol. The collected samples are dried in an oven at 60°C for 12 hours to obtain a green powder solid sample, namely NiZn-MOF. (3) Spread the NiZn-MOF obtained in the previous step evenly in a covered corundum porcelain boat, place it in a tubular furnace, heat it to different temperatures at a heating rate of 5°C / min and keep it warm for 1 hour. After heating, cool it to room temperature, take out the carbonized sample, and obtain NiZn-MOF-derived carbon, called Ni 0.7 Zn 0.3 O / Cx. (4) Ni 0.7 Zn 0.3 Preparation of O / Cx cathode electrode: Cut the hydrophobic carbon paper into 1x2cm size, and use ACE, DI, and EtOH for 20min to remove the surface oil, and finally dry it in an oven at 60℃ for 1h. 0.7 Zn 0.3 After O / Cx, Nafion, IPA, and DI are prepared in a certain proportion, they are ultrasonically dispersed for 1 hour to make them uniformly dispersed. A certain amount of ink is extracted and evenly coated on carbon paper. (5) Assembly of H-type electrolytic cell: A standard three-electrode system is used in an H-type electrolytic cell with a proton exchange membrane as the diaphragm. 0.7 Zn 0.3 The Ox cathode electrode was used as the working electrode, SCE as the reference electrode, Pt sheet as the counter electrode, and the electrolytic cell solution was 120 mL of O2-saturated 0.1 M KOH solution. O2 was continuously introduced during the reaction, and H2O2 was synthesized by electrocatalytic reaction at a specific potential for 1 h.

2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of zinc nitrate to nickel acetate is 0:3, 2:1, 3:0 and 16.8 mg terephthalic acid.

3. The preparation method according to claim 1, characterized in that: In step (1), the total amount of DMAC and ethanol is 25.6 ml (5:3).

4. The preparation method according to claim 1, characterized in that: The temperatures in step (3) are 350°C / 450°C / 550°C respectively.

5. The preparation method according to claim 1, characterized in that: In step (4), the ink is prepared as a catalyst in the following proportions: Nafion: IPA: DI = 10 mg: 40 μL: 120 μL: 40 μL.

6. The preparation method according to claim 1, characterized in that: In step (5), the potentials were selected as 0.2 / 0.3 / 0.4 / 0.5 / 0.6 (vs. RHE).